Effects of feeding purple rice (oryza sativa L. Var. Glutinosa) on the quality of pork and pork products - Sanchai Jaturasitha (2018)
© 2016 by Asian-Australasian Journal of Animal Sciences. Purple rice is a strain of glutaneous rice rich in anthocyanins and γ-oryzanol. Both types of compounds are involved in antioxidant and lipid metabolism of mammals. Three experimental diet types were used which consisted approximately by half either of purple rice, white rice or corn. Diets were fed to 3∼10 pigs growing from about 30 to 100 kg. Meat samples were investigated either as raw or cured loin chops or as smoked bacon produced from the belly. Various physicochemical traits were assessed and data were evaluated by analysis of variance. Traits describing water-holding capacity (drip, thaw, and cooking losses) and tenderness (sensory grading, shear force) of the meat were mostly not significantly affected by the diet type. However, purple rice feeding of pigs resulted in lower fat and cholesterol contents of loin and smoked bacon compared to white rice, but not compared to corn feeding except of the fat content of the loin. The shelf life of the raw loin chops was improved by purple rice as well. In detail, the occurrence of thiobarbituric acid reactive substances after 9 days of chilled storage was three to four times higher in the white rice and corn diets than with purple rice. The n-6:n-3 ratio in the raw loin chops was 9:1 with purple rice and clearly higher with 12:1 with the other diets, meat lipids. Level and kind of effect of purple rice found in raw meat was not always recovered in the cured loin chops and the smoked bacon. Still the impression of flavor and color, as well as overall acceptability were best in the smoked bacon from the purple-rice fed pigs, whereas this effect did not occur in the cured loin chops. These findings suggest that purple rice has a certain, useful, bioactivity in pigs concerning meat quality, but some of these effects are of low practical relevance. Further studies have to show ways how transiency and low recovery in meat products of some of the effects can be counteracted.